Reassessment of Dianous ponticus Fagel, 1963 (Staphylinidae: Steninae) and the genus Dianous in Turkey: Taxonomic, ecological, and distributional insights - Turan, Yavuz (Zootaxa, 2025)
Dianous ponticus Fagel, 1963 is redescribed based on newly collected specimens from various localities in Turkey. The original description lacked sufficient diagnostic morphological and genital characters, which are here provided in detail, including precise morphometric data and images of habitus and genital characters. Previously, the species was known only from the Eastern Black Sea Region; however, the present study significantly expands its known distribution to include the Central and Western Black Sea Regions as well. Detailed locality information, elevation ranges, collection months, and habitat characteristics are presented. In addition to the redescription of D. ponticus, a faunistic overview of the genus Dianous in Turkey is provided. The checklist includes all currently known species and subspecies from the country. Distributional gaps are identified, and potential areas for future research are discussed. Phenological patterns and altitudinal variation are also analyzed, suggesting seasonal shifts in activity and elevation. A distribution map is included to offer an updated perspective on the range of D. ponticus in Turkey and to support further ecological and taxonomic investigations within the genus.